Unilateral Facilitation Does Not Raise International Labor Migration from the Philippines - Beam, Emily; McKenzie, David; Yang, Dean (World Bank, Washington, DC, 2014)
Significant income gains from migrating from poorer to richer countries have motivated unilateral (source-country) policies facilitating labor emigration. However, their effectiveness is unknown. The authors conducted a large-scale randomized experiment in the Philippines testing the impact of unilaterally facilitating international labor migration. The most intensive treatment doubled the rate of job offers but had no identifiable effect on international labor migration. Even the highest overseas job-search rate that was induced (22 percent) falls far short of the share initially expressing interest in migrating (34 percent). The paper concludes that unilateral migration facilitation will at most induce a trickle, not a flood, of additional emigration.